The Influence of Internal Control System on Information Quality in Regional Financial Reporting in Barru Regency - Aminah, A. (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal